CRUSTAL STRUCTURE BETWEEN THE KNIPOVICH RIDGE AND THE VAN MIJENFJORDEN (SVALBARD) - Ritzmann O.; Mjelde R.; Jokat W.; Shimamura H. (My University, 2002)
The Alfred Wegener Institute of Polar and Marine Research, the University of Bergen and Hokkaido University acquired new seismic refraction data along a transect from the Knipovich Ridge to the inner Van Mijenfjorden in southern Svalbard. A close spacing of on- and offshore receivers and a dense marine shot pattern provide the data for a high resolution p-wave velocity model for geological interpretation. Additional new seismic reflection data (University of Bergen) yield structural information for a more reliable analysis. Crustal thickness along the Van Mijenfjorden is 33 to 34 km. Seismic velocities of 5.0 km/s are observed within the upper crustal section of the Tertiary Central Spitsbergen Basin. A Paleozoic sedimentary basin with a depth of 8 to 10 km is associated with the Nordfjorden Block. The seismic velocities are up to 6.0 km/s. Paleozoic sedimentary rocks are expected further to the west of the Hornsund Lineament since seismic velocities reveal a similar range here. West of the Bellsund the continental crust thins gradually over a 90 km wide rifted zone.